1998
DOI: 10.1001/archpsyc.55.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Signs and Symptoms in Schizophrenia

Abstract: Depressive signs and symptoms in schizophrenia are responsive to treatment. The pleotrophic pharmacological features of olanzapine, through 1 or more non-D2-mediated pathways, likely contribute to its superior treatment effect. Better control of the mood disorders accompanying schizophrenia holds the possibility for improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(38 citation statements)
references
References 52 publications
0
34
1
3
Order By: Relevance
“…These symptoms are treated, to varying degrees, with antidepressant drugs [37,38], second-generation antipsychotics including clozapine and olanzapine [39,40,41], and muscarinic antagonists [42,43]. The same drugs have been used to reduce immobility times in the forced swimming test [20,44,45,46], and, as shown here, they significantly reduce immobility in C. elegans .…”
Section: Discussionmentioning
confidence: 97%
“…These symptoms are treated, to varying degrees, with antidepressant drugs [37,38], second-generation antipsychotics including clozapine and olanzapine [39,40,41], and muscarinic antagonists [42,43]. The same drugs have been used to reduce immobility times in the forced swimming test [20,44,45,46], and, as shown here, they significantly reduce immobility in C. elegans .…”
Section: Discussionmentioning
confidence: 97%
“…1417 The American Psychiatric Association Clinical Practice Guidelines assigned a level II evidence for a recommendation on the use of SGAs for the treatment of depression in schizophrenia not associated with relapse. 12 While some studies suggest a specific antidepressant effect for SGAs, and for olanzapine in particular, mediated through 1 or more non-D 2 pathways, 15 others have suggested that the difference detected in some studies may have reflected akinesia due to a lack of prophylactic anticholinergic medication in the FGA arm of the studies involving moderate to high doses of the high-potency drug haloperidol. 18 It has also been suggested that in drug-naive patients, depression in schizophrenia is related to low presynaptic dopamine function.…”
mentioning
confidence: 99%
“…We found that clozapine demonstrated superior effect over quetiapine on the CDSS items of depression (p < .01), hopelessness (p = .01), self-depreciation (p = .01), guilty ideas of reference (p < .01), pathological guilt (p < .01), morning depression (p = .02), and observed depression (p = .01). Further, considering the likelihood that improvement in depressive symptoms may be influenced by that in positive or negative symptoms (Tollefson et al, 1998), we calculated Pearson product-moment correlation coefficients between changes in the CDSS and PANSS Positive or Negative score in the clozapine group, using the last observation carried forward (LOCF). However, no correlation was found between changes in the CDSS and PANSS Positive or Negative score (r = 0.04, p = .81; r = 0.15, p = .32, respectively).…”
Section: Resultsmentioning
confidence: 99%